2020
DOI: 10.1002/cam4.2848
|View full text |Cite
|
Sign up to set email alerts
|

Initial results of a novel technique of clipped node localization in breast cancer patients postneoadjuvant chemotherapy: Skin Mark clipped Axillary nodes Removal Technique (SMART trial)

Abstract: Purpose Removal of clipped nodes can improve sentinel node biopsy accuracy in breast cancer patients post neoadjuvant chemotherapy (NACT). However, the current methods of clipped node localization have limitations. We evaluated the feasibility of a novel clipped node localization and removal technique by preoperative skin marking of clipped nodes and removal by the Skin Mark clipped Axillary nodes Removal Technique (SMART), with the secondary aim of assessing the ultrasound visibility of the various clips in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 22 publications
0
27
0
1
Order By: Relevance
“…Limitations include a small sample size and additional cost that may be incurred secondary to multiple nodal localization devices; however, this may be negated by the cost of sentinel lymph node biopsy, which was omitted. SMART is a novel inexpensive technique [9] that can be used for removal of multiple clipped nodes, but it has limitations. A cost analysis will require future studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Limitations include a small sample size and additional cost that may be incurred secondary to multiple nodal localization devices; however, this may be negated by the cost of sentinel lymph node biopsy, which was omitted. SMART is a novel inexpensive technique [9] that can be used for removal of multiple clipped nodes, but it has limitations. A cost analysis will require future studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, because sentinel lymph node biopsy was omitted, this additional cost may be negated by the cost of the sentinel lymph node biopsy mapping agents [17]. Skin mark clipped axillary nodes removal technique (SMART) is a recently described technique [9] that could be used for the removal of multiple clipped nodes with minimal cost. However, it is not ideal for the removal of more than two deeply seated clipped nodes.…”
mentioning
confidence: 99%
“…Portnow et al [ 15 ] reported the US visibility of four types of tissue markers—including UltraCor Twirl and UltraClip—in animal tissue models stimulating axillary echotexture, and UltraCor Twirl demonstrated the highest score on the grading system used by radiologists. Lim et al [ 14 ] reported that UltraCor Twirl showed the best US visibility and highest excision rate after NAC among the four different types of tissue markers, including UltraCor Twirl and UltraClip, in 14 patients. Our study results support those of previous studies; however, we investigated a larger number of patients and analyzed the visibility in the absence of residual suspicious lymph nodes on US after NAC.…”
Section: Discussionmentioning
confidence: 99%
“…However, US-guided localization of axillary lymph nodes after a partial or complete radiologic response to neoadjuvant chemotherapy may often be challenging to radiologists [ 12 , 13 ]. A few studies have reported the US visibility of tissue markers for axillary lymph node localization in animal model phantoms or in a small number of patients with different types of tissue markers [ 14 , 15 ]. However, to the best of our knowledge, no study has evaluated the visibility of tissue markers in metastatic axillary lymph nodes after showing a pCR on US.…”
Section: Introductionmentioning
confidence: 99%
“…Removal of clipped metastatic nodes can improve the accuracy of axillary staging in breast cancer patients after neo-adjuvant chemotherapy (NAC). 1 Various clips have been used in this setting, but the appearance of the clips on magnetic resonance imaging (MRI) and factors affecting their visibility have not been widely examined. We aimed to compare the visibility of various clips in axillary nodes on MRI and to determine the technical factors which may affect their visualization.…”
mentioning
confidence: 99%